Analisis Faktor Penyebab Rendahnya Minat Siswa Terhadap Tari Tradisional Mata Pelajaran Seni Budaya dan Prakarya - Wati, Diana Ambar; Burhanuddin, Afid; Ardhyantama, Vit (Scholarly Journal of Elementary School, 2022)
This study aims to describe: (1) internal factors that can affect students' low interest in traditional dance in arts and crafts subjects at SD Negeri 3 Donorojo (2) external factors that can affect students' low interest in traditional dance in arts and culture subjects and crafts at SD Negeri 3 Donorojo. This type of research is descriptive qualitative research. Collecting data in the form of observations, interviews, questionnaires, and documentation. The validity of the data used triangulation techniques and continued with data analysis using the Miles and Huberman model. The data analysis used includes data reduction, data presentation and conclusion drawing. Interviews were used to collect data given to teachers of arts and culture and crafts. The results showed that: (1) the internal factors that can influence are psychological factors, namely 8 students feel happy to participate in dance learning and 9 students are not happy to participate in dance learning, for 10 students have difficulty in participating in learning and 7 students have no difficulty. (2) external factors that can influence are family factors, namely the lack of parenting and attention to students during the learning process, school factors, namely the teacher's strategy in teaching is less effective and fun and inadequate infrastructure facilities, and community factors, namely different friends. hobbies and can influence students in terms of interests.